Low‐dose rituximab and concurrent adjuvant therapy for pemphigus: Protocol and single‐centre long‐term review of nine patients. (17th February 2017) - Robinson, Aaron J; Vu, Mi; Unglik, Gary A; Varigos, George A; Scardamaglia, Laura
Abstract: Pemphigus is an autoimmune B‐cell mediated blistering disease associated with significant morbidity and mortality. Rituximab has proven effective for the treatment of steroid‐refractory pemphigus, although there is controversy over the optimum dosing protocol. Additionally, effective disease control often requires long‐term immunosuppression, even in disease‐free periods. We present a case series of a single‐centre long‐term follow up of nine patients with pemphigus, treated with two 500‐mg doses of rituximab separated by 14 days along with concurrent adjuvant therapy. In all these patients, low‐dose rituximab resulted in B‐cell depletion, along with a reduction in blistering disease. Three of these patients required repeat dosing cycles due to either relapsed disease or incomplete disease control following the first dosing cycle, and have remained disease free up to 154 weeks thus far. Six patients developed minor infections during the course of their treatment, but no major complications were observed.